Paternidade na adolescência no contexto dos serviços de saúde, escola e comunidade: uma perspectiva bioecológica - Bordignon, Simoní Saraiva (2012)
The fatherhood during the adolescence means experiencing a process of transformations and (re) constructions, in search of identity for this man who is still a teenager, as well as for his family. In this context, fatherhood is considered a social role and its development happens by means of the interactions established between the individuals and the environment. The interactions are fundamental components through which people interfere with the behavior of each other, making it possible to develop the human being. This study is justified in seeking to fill the theoretical gap on the issue, since there is a shortage of data that could describe the co-responsible subjects for pregnancy during the adolescence and contribute to modify interactions established by teachers, health professionals, who, often, fail to address of an integral and citizen way the teenage father. Thus, we had as goal: know about the perception of teenage fathers with regard to their interaction with the health service, school and community. This is a study with qualitative approach, exploratory descriptive, constituent of a multi-centric research which is entitled "Social Networks of Support to the Fatherhood in Adolescence". Data collection was performed from June 2009 to June 2010 in the city of Pelotas / RS / Brazil. The respondents were 14 teenager fathers, selected by appointment of teenage puerperal women. The semistructured interviews were conducted in the homes of these subjects, six months after the birth of the child. Through Discursive Textual Analysis and the theoretical referential of Urie Bronfenbrenner, three categories were built. Interaction between the fatherhood and the school: it has showed that teenage fathers refer to valorize the formal education, due it provides a greater benefits for the upbringing of their children and better life conditions for their family, they also recognize the difficulties of balancing the work, study and care of their children and, even those who were not attending school because of work reasons, longed to return to the classroom, location where they pointed out having spent much time of their lives; Regarding the parental interaction established with the health services: the majority of teenage fathers demonstrated to be extremely committed to the care of their children at the Basic Health Unit, claiming that follow expressively the routine consultations, with a willingness to understand the care oriented and discuss on the healthy strategies to be acquired, in an autonomous and independent manner, even stating that, sometimes, they were unable to follow up the consultations due to their work. In the category Paternal interactions experienced in the community: some subjects claimed to continue with their leisure activities, such as playing soccer, attending a samba school, while others refer to feel excluded by their friends and meet difficulties of acceptance in the community ambit. It is possible to conclude that the teenage fathers showed themselves receptive to the formal studies, present and participatory in the health services and in community. Thus, difficulties of interaction with the school, health services and community do not seem to be arising from the insertion of teenagers in the researched environments, but from organization and suitable preparation for the welcome of these teenagers.